Antonio Muñoz Molina, un Robinson en Manhattan - Castellani, Jean-Pierre (Revista de Filología Románica, 2006)
In the literature of travel to foreign cities, writers’ travel diaries have always been a source of subjective witness and served as the basis for hybrid texts falling between the personal diary, essays and journalism. Ventanas de Manhattan by Antonio Muñoz Molina provides a particularly significant example of this kind of litterature, halfway between document and fiction. From the chronicles of his Robinson urbano in Grenada to this tale of a visit to New York, Muñoz Molina has always been fascinated by the discovery of a new territory, like Robinson on his island, developing it into a veritable poetics of the city. Impressionistic flashes running through the most mysterious corners of the great city and chaotic encyclopedia of the city.